Lessons Learnt From the Experiences of Primary Care Physicians Facing COVID-19 in Benin: A Mixed-Methods Study - Bello, Kéfilath; De Lepeleire, Jan; Agossou, Christian; Apers, Ludwig; Zannou, Djimon Marcel; Criel, Bart (Frontiers in Health Services, 2022)
Introduction: In sub-Saharan Africa, there is a need to better understand and guide the practice of primary care physicians (PCPs), especially in a crisis context like the COVID-19 pandemic. This study analyses the experiences of PCPs facing COVID-19 in Benin and draws policy lessons. Methods: The study followed a fully mixed sequential dominant status design. Data were collected between April and August 2020 from a sample of PCPs in Benin. We performed descriptive analyses on the quantitative data. We also performed bivariate analyses for testing associations between various outcomes and the public/private status of the PCPs, their localization within or outside the cordon sanitaire put in place at the beginning of COVID-19, and their practice' category. A thematic content analysis was done on qualitative data. Results from both analyses were triangulated. Results: Ninety PCPs participated in the quantitative strand, and 14 in the qualitative. The median percentage of the COVID-19 control measures implemented in the health facilities, as reported by the PCPs, was 77.8% (interquartile range=16.7%), with no difference between the various groups. While 29.4% of the PCPs reported being poorly/not capable of helping the communities to deal with COVID-19, 45.3% felt poorly/not confident in dealing with an actual case. These percentages were bigger in the private sector. The PCPs' experiences were marked by anxiety and fear, with 80.2% reporting stress. Many PCPs (74.1%) reported not receiving support from local health authorities, and 75.3% felt their concerns were not adequately addressed. Both percentages were higher in the private sector. The PCPs especially complained of insufficient training, insufficient coordination, and less support to private providers than the public ones. For 72.4% and 79.3% of the PCPs, respectively, the pandemic impacted services utilization and daily work. There were negative impacts (like a decrease in the services utilization or the quality of care), but also positive ones (like improved compliance to hygiene measures and new opportunities). Conclusion: Our study highlighted the need for more structured support to PCPs for optimizing their contribution to epidemics control and good primary healthcare in Benin. Efforts in this direction can build on several good practices and opportunities.